2020
DOI: 10.1038/s41598-020-72688-y
|View full text |Cite
|
Sign up to set email alerts
|

The fatty-acid amide hydrolase inhibitor URB597 inhibits MICA/B shedding

Abstract: MICA/B proteins are expressed on the surface of various types of stressed cells, including cancer cells. Cytotoxic lymphocytes expressing natural killer group 2D (NKG2D) receptor recognize MICA/B and eliminate the cells. However, cancer cells evade such immune recognition by inducing proteolytic shedding of MICA/B proteins. Therefore, preventing the shedding of MICA/B proteins could enhance antitumor immunity. Here, by screening a protease inhibitor library, we found that the fatty-acid amide hydrolase (FAAH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Yet another work showed that inhibition of endogenous AEA degradation enhanced interaction with the tumour immune system. Accordingly, the FAAH inhibitor URB597 suppressed the shedding of the proteins major histocompatibility complex class I polypeptide-related sequence A (MICA) and B (MICB) on the surface of human HCC cells [ 137 ]. Since MICA/B proteins are recognised by cytotoxic lymphocytes expressing the natural killer group 2D (NKG2D) receptor and tumour cells are subsequently eliminated, preventing the shedding of MICA/B proteins can improve antitumour immunity.…”
Section: Interactions With the Immune Systemmentioning
confidence: 99%
“…Yet another work showed that inhibition of endogenous AEA degradation enhanced interaction with the tumour immune system. Accordingly, the FAAH inhibitor URB597 suppressed the shedding of the proteins major histocompatibility complex class I polypeptide-related sequence A (MICA) and B (MICB) on the surface of human HCC cells [ 137 ]. Since MICA/B proteins are recognised by cytotoxic lymphocytes expressing the natural killer group 2D (NKG2D) receptor and tumour cells are subsequently eliminated, preventing the shedding of MICA/B proteins can improve antitumour immunity.…”
Section: Interactions With the Immune Systemmentioning
confidence: 99%
“…Therefore, MMP inhibitors (MMPI) constitute attractive candidates, which is further supported by the finding that mouse prostate tumors engineered to express a shedding-resistant noncleavable MICB did not grow when implanted into SCID mice but treatment of the animals with an NKG2D blocking mAb led to the development of tumors ( 304 ). Several MMPI such as MMPI-I ( 116 , 305 ), MMPI-II ( 117 ), MMPI III ( 117 , 271 ), MMPI-IV ( 306 ), batimastat or BB94 ( 117 , 307 ), GW280264X ( 117 , 301 ), GI1254023X ( 117 ), ilomastat or GM6001 ( 117 , 301 , 308 ), URB597 ( 309 ), periostat or doxycycline ( 310 ) and some ADAM-10 selective inhibitors ( 311 , 312 ) can inhibit MICA/B shedding in vitro , resulting in a heightened cell surface expression of the NKG2DL and an increase in NK cell-mediated cytotoxicity. However, among these compounds, only periostat is currently in clinical trials for different types of tumors ( 313 ).…”
Section: Rational Design Of Combination Therapies That Target the Nkg2d-nkg2dl Axismentioning
confidence: 99%
“…Accumulating data suggest that the endocannabinoid system acts as an important regulator of tumour immune defence through multiple mechanisms. For example, the involvement of the endocannabinoid system in the immune response of tumours was recently highlighted by the finding that the FAAH inhibitor URB597 may enhance the immune surveillance of human hepatocellular carcinoma cells [162]. Specifically, URB597 via induction of TIMP-3 expression was found to inhibit proteolytic shedding of the proteins major histocompatibility complex class I polypeptide-related sequence A (MICA) and B (MICB) on the surface of cancer cells, thereby ensuring binding of these proteins to the natural killer group 2D (NKG2D) receptor on the surface of cytolytic lymphocytes and subsequent killing of tumour cells.…”
Section: Effect Of Faah and Magl Inhibition On Tumour-immune Interactionsmentioning
confidence: 99%